A Review of Rabbit Diseases in Egypt - Hamed A Mohammed; Eid AA M; El-Bakrey R MM (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Promising approaches of the Egyptian governmental as well as non-governmental society to rabbit industry to overcome the unemployment of youth in the society required more efforts from scientific institutes to help in development of such industry. Epidemiological studies are of outmost importance to highlight disease nature and to help in meantime implement of successful preventive and control measures. The aim of this paper is to review the situation of rabbit diseases of economic impact in Egypt (1952 to 2013). The review will highlight the viral infection of rabbit hemorrhagic disease, bacterial disease of colibacillosis, clostridiosis, salmonellosis, pasteurellosis, staphylococcosis and listeriosis and parasitic infection of coccidiosis and mange.   Key words: Rabbit, disease, bacteria, viral infection